IMPLEMENTASI MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS IV SEKOLAH DASAR - Sumiati, Sumiati (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2025)
ABSTRACT The background of this research stems from the low science learning outcomes of fourth-grade students at SDN Leuwibatu 06, which is attributed to conventional teaching methods that do not actively engage students. To address this issue, it is necessary to implement an improved learning model, such as the cooperative Make A Match model. This study aims to determine the implementation of the Make A Match learning model to improve students' learning outcomes in science subjects in Grade IV at SDN Leuwibatu 06. The Make A Match cooperative learning model was applied through Classroom Action Research (CAR). The model used was that of Kemmis and McTaggart, which was carried out in two cycles, each consisting of the stages of planning, action, observation, and reflection. The results of the study showed an improvement in the science learning outcomes of fourth-grade students at SDN Leuwibatu 06 after applying the Make A Match cooperative learning model. This is evident from the results in the pre-cycle, where the average score was 59.08, then increased to 66.71 in the first cycle, and further improved to 73.03 in the second cycle, with the Minimum Mastery Criteria (KKM) set at 65. As for learning mastery, in the pre-cycle it was 29.0%, which increased to 55.3% in the first cycle and then to 86.8% in the second cycle. Student activity in the first cycle reached 74.34%, and in the second cycle increased to 87.99%. ABSTRAK Latar belakang penelitian ini berangkat dari rendahnya hasil belajar IPA siswa Kelas IV SDN Leuwibatu 06 akibat pembelajaran yang masih bersifat konvensional dan kurang melibatkan siswa secara aktif. Untuk mengatasinya, diperlukan pembaruan model pembelajaran, salah satunya melalui penerapan model Make A Match (membuat pasangan). Penelitian ini bertujuan untuk mengetahui implementasi model pembelajaran make a match untuk meningkatkan hasil belajar siswa pada mata pelajaran IPA di kelas IV SDN Leuwibatu 06. Model pembelajaran kooperatif tipe make a match menggunakan Penelitian Tindakan kelas (PTK). Model yang digunakan adalah dari Kemmis dan Mc Taggart yang dilaksanakan dalam dua siklus, yang masing-masing siklus terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi. Hasil penelitian menunjukan bahwa adanya peningkatan hasil belajar IPA siswa kelas IV SDN Leuwibatu 06 setelah menggunakan model pembelajaran kooperatif tipe make a match. Hal ini Nampak dari hasil pada prasiklus yaitu rata-rata sebesar 59,08 kemudian pada siklus I menjadi 66,71 dan pada siklus II meningkat menjadi 73,03 dengan Kriteria Kentuntasan Minimum (KKM) sebesar 65. Adapun ketuntasan belajar pada pra siklus sebesat 29,0%, pada siklus I meningkat menjadi 55,3% dan siklus II meningkat menjadi 86,8%. Aktivitas siswa pada siklus I mencapaai 74,34% dan pada siklus II meningkat menjadi 87,99%.